Development and Implementation of Didactic Sequences for Second Order ODEs: Practical Applications with GeoGebra: Desenvolvimento e Implementaçã de Sequências Didáticas para EDOs de Segunda Ordem: Aplicações Práticas com GeoGebra - Pimentel Paiva, Ana Carla (2024)
Second Order Ordinary Differential Equations are a subject considered in the traditional approach to the theory of Ordinary Differential Equations - ODE. This article describes, in particular, two stages foreseen by Didactic Engineering – ED: the phases of preliminary analysis and a priori analysis. Activities described/structured with the support of technology are emphasized. Mediation affected by the appropriate exploitation of software makes it possible to avoid certain elements that act as obstacles to a broad understanding, inherent to these equations. In this way, we indicate and structure problem situations in Geogebra, in order to use visualization to understand qualitative properties (graphic-geometric) and not just algorithmic ones. Thus providing the description of factors relevant to the didactic mediation of second- order differential equations.